Optogenetic control of transition to metamorphosis - Changyuan Wang; Denis F. Faerberg; Yuka Sekine; Takeaki Ozawa; John J. Tyson; Robert A. Marmion; Stanislav Y. Shvartsman (Proceedings of the National Academy of Sciences, 2026)
System identification approaches are commonly used in engineering to infer simple yet predictive models of complex systems from their responses to time-dependent perturbations. Here, we apply this strategy at the whole organism scale, establishing a predictive model of commitment to metamorphosis in Drosophila . At this critical point in animal development, the larva stops feeding and proceeds to take on the adult form. The neuroendocrine circuits governing commitment to metamorphosis assess the growth and patterning programs, eventually triggering the production of systemic hormones that terminate growth and initiate metamorphosis. Previous studies of these circuits relied on relatively static genetic perturbations and starvation experiments. Here, we take advantage of optogenetic approaches in Drosophila to flexibly perturb a key signaling node within the endocrine gland in otherwise undisturbed larvae. We used this approach to infer parameters in a compact mathematical model and demonstrate that it makes accurate predictions of larval commitment to metamorphosis. Our work paves the way for quantitative studies of other juvenile-to-adult transitions, including mammalian puberty, which relies on strikingly similar mechanisms.